Pelestarian Bahasa Jawa dalam Komunikasi Sehari-hari Antar Komunitas Imigran di Legoso, Ciputat - Mayasari, Ira (Neolectura, 2023)
This research aims to analyze the process of preserving the Javanese language in the context of language shift occurring among the immigrant community in Legoso, Ciputat. Language shift often occurs due to high mobility, potentially leading to the loss of the first language (L1) and possibly triggering its extinction. This condition demands efforts in language preservation to maintain cultural and linguistic identity. A qualitative descriptive method, utilizing techniques like free listening involving conversation and interviews, was employed in this study to gain a deep understanding of the existing forms of Javanese language preservation, including the use of Javanese ngoko, kromo, and their combinations. Furthermore, this study explores the function of preserving the Javanese language in Legoso, Ciputat, which includes ease of communication and strengthening familial relationships among the immigrant community. The results of this research are expected to provide insights into the importance of language preservation efforts in a multicultural and high mobility context, as well as contriMrs.te to strategies for maintaining and conserving language and culture.